(untitled) (Palestine Technical College Journal for Research and Studies, 2020)
The study aimed to identify the status of training in the Ministry of Interior and National Security in Gaza, the training methods that are appropriate for its work, and the problems facing training in it. The study used the descriptive analytical approach, and the questionnaire was used as a tool for the study, and targeted all officers with high ranks and holders of university degrees and have administrative positions, which were (1089) officers, and distributed to a random sample stratified (320) officers, and recovered (289) questionnaires accounted for (90.30%), the study concluded that the reality of training is represented by the following areas: (Management support – Identifying training needs – Planning the training process – Training methods used – Training environment – Selection of trainers – evaluation of training process) has obtained the agreement of respondents by (75.83%), and the training methods that fit the work of the ministry obtained the agreement of respondents by (81.13%), and were in the order: (lecture – practical application – planned discussion – case study – training in work – field trip), and that the problems facing the training got the consent of the respondents by (79.37%), and were in the order: (lack of financial and material resources – vacations and emergency – poor opportunities for exchange of expertise – poor employee willingness to train – weak professionalism in the identification of training needs – weakness of the trainers’ experience), the study recommended allocation of an item in the general budget of the Ministry for the training process, designing programs to identify training needs with the participation of employees, enhancing the practical aspect of training programs.